PENGARUH AGNES MONICA SEBAGAI CELEBRITY ENDORSER TERHADAP PEMBENTUKAN BRAND IMAGE HONDA VARIO - Rini, Endang Sulistya; Astuti, Dina Widya (BISMA: Jurnal Bisnis dan Manajemen, 2012)
The Objective of this research would be to know the effect of celebrityendorser, Agnes Monica, on brand image formation of Honda Vario for student indepartment of management, North Sumatra University. The method of analysisused are descriptive analysis and multiple linear regression. The result of researchindicated that, through descriptive analysis result, it could be seen that almost allstudent agreed that Agnes Monica could form a brand image of Honda Vario. Butthrought multiple linear regression, the result of research indicated that thepositive and significant effects were from variables of visibility, credibility,attraction and power on brand image, based on t-test, variable of power was themost dominant variable in forming the brand image.